2012
DOI: 10.1007/s11130-012-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

Color and Antioxidant Characteristics of Some Fresh Fig (Ficus carica L.) Genotypes from Northeastern Turkey

Abstract: Fruit skin color, total phenolics, total anthocyanins, soluble solids content, titratable acidity and total antioxidant capacity in fresh fruits of a number of local and well-known fig (Ficus carica L.) genotypes and cultivars grown in northeastern Turkey were determined. TEAC (Trolox equivalent antioxidant capacity) and FRAP (ferric reducing antioxidant power) assays were used to determine total antioxidant capacity. Fruit skin color of genotypes were found to be very diverse, i.e., light green, light purple,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 31 publications
6
60
1
3
Order By: Relevance
“…In fact, only cyanidin‐3‐O‐rutinoside and vanillic acid derivative were identified in these samples. The results for total phenolic compounds obtained from our samples are comparable with the data reported by previously published studies (Vinson and others ; Caliskan and Polat ; Ercisli and others ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, only cyanidin‐3‐O‐rutinoside and vanillic acid derivative were identified in these samples. The results for total phenolic compounds obtained from our samples are comparable with the data reported by previously published studies (Vinson and others ; Caliskan and Polat ; Ercisli and others ).…”
Section: Resultssupporting
confidence: 92%
“…Many studies were found in literature about the antioxidant activity of polyphenols in fruits and vegetables (Gil and others ; Ismail and others ; Bao and others ), whereas figs have not been extensively studied. Some papers report the determination of total phenolics (Vinson ; Vinson and others ; Solomon and others ; Caliskan and Polat ; Ercisli and others ), while others deal with the characterization of the individual phenolic compounds (Del Caro and Piga ; Veberic and others ; Vallejo and others ).…”
Section: Introductionmentioning
confidence: 99%
“…These herbals were based on ancient Greek authors, especially Dioscorides ( De Materia Medica , BC 78–77) and Galen, as also on references of Hippocrates ( Corpus Hippocratium: On Ancient Medicine, On Aliment or Nutriment , BC 460–377) appreciating fig as a phytonutrient. Its medicinal benefits include metabolic, cardiovascular, antispasmodic, antiviral, antioxidant, antibacterial and anti‐inflammatory remedies, as also potential anticancer activity …”
Section: Introductionmentioning
confidence: 99%
“…The 10,000 cc OTR film at 8°C and 30,000 cc OTR film at 24°C treatments had the highest antioxidant and vitamin C content. Antioxidants neutralize chemically active metabolic products, such as free radicals, inducing serious cellular damage (Ercisli et al 2012). The 10,000 cc OTR film at 8°C and 30,000 cc OTR film at 24°C treated Ligularia will have the best shelf life.…”
Section: Leaf Quality Parametersmentioning
confidence: 99%